Bibliometric Analysis of Research History, Hotspots, and Emerging Trends on Flax with CiteSpace (2000-2022). Issue 1 (31st December 2023) - Gao, Shuaishuai; Chen, Su; Huang, Rong; Guo, Yuan; Qiu, Caisheng; Long, Songhua; Wu, Zhimin; Wang, Weidong; Qiu, Huajiao; Zhao, Xinlin; Wang, Yufu
ABSTRACT: With the growing health and environmental consciousness, flax ( Linum usitatissimum L.) has attracted more attention owing to its great potential in the food, health care, and material industry. For such an important crop, it is crucial to understand its development history, current status, and hotspots and finally find the future directions of flax research. This paper mainly analyzed the published articles (collected from the Web of Science) related to flax from 2000–2022 and the cited references by these articles using the software of CiteSpace. Results showed that the number of studies on flax kept increasing and increased rapidly from 2010 to 2022. Canada and France are the leading countries in flax research with more than 970 articles published during the period. By analyzing the high-frequency keywords, five important research areas were found: (1) flax fiber quality and its application in composites, (2) chemical composition and products of flaxseed, (3) tolerance of flax to stress and genetics, (4) cellulose and lignin, (5) fiber-reinforced composites and flax fabric. With the strongest citation bursts, bio-composite with flax straw has become the hottest research area for flax. In the future, efforts should still be made to the simplified and efficient production of flax owing to the higher labor cost, and more attention should be paid to healthier flaxseed food and flax-based environmentally friendly biomaterials. Finally, decreasing the cost of cultivation and pre-processing and developing end products with higher values would greatly promote the development of the whole flax industry.